Quorum Sensing and Metabolic State of the Host Control Lysogeny-Lysis Switch of Bacteriophage T1 - Leanid Laganenka (American Society for Microbiology, 2019)
ABSTRACT Bacterial viruses, or bacteriophages, are highly abundant in the biosphere and have a major impact on microbial populations. Many examples of phage interactions with their hosts, including establishment of dormant lysogenic and active lytic states, have been characterized at the level of the individual cell. However, much less is known about the dependence of these interactions on host metabolism and signal exchange within bacterial communities. In this report, we describe a lysogenic state of the enterobacterial phage T1, previously known as a classical lytic phage, and characterize the underlying regulatory circuitry. We show that the transition from lysogeny to lysis depends on bacterial population density, perceived via interspecies autoinducer 2. Lysis is further controlled by the metabolic state of the cell, mediated by the cyclic-3′,5′-AMP (cAMP) receptor protein (CRP) of the host. We hypothesize that such combinations of cell density and metabolic sensing may be common in phage-host interactions. IMPORTANCE The dynamics of microbial communities are heavily shaped by bacterium-bacteriophage interactions. But despite the apparent importance of bacteriophages, our understanding of the mechanisms controlling phage dynamics in bacterial populations, and particularly of the differences between the decisions that are made in the dormant lysogenic and active lytic states, remains limited. In this report, we show that enterobacterial phage T1, previously described as a lytic phage, is able to undergo lysogeny. We further demonstrate that the lysogeny-to-lysis decision occurs in response to changes in the density of the bacterial population, mediated by interspecies quorum-sensing signal AI-2, and in the metabolic state of the cell, mediated by cAMP receptor protein. We hypothesize that this strategy enables the phage to maximize its chances of self-amplification and spreading in bacterial population upon induction of the lytic cycle and that it might be common in phage-host interactions.